Changes of 8-OHdG and TrxR in the Residents Who Bathe in Radon Hot Springs - Gao Yanxiao; Tian Mei; Gao Gang; Wang Xiaochun; Liu Jianxiang (SAGE Publishing, 2019)
This study explored the effects of long-term bathing in radon hot springs on oxidative damage and antioxidation function in humans. In this study, blood was collected from residents in the Pingshan radon hot spring area (RHSA), Jiangzha RHSA, and control area (CA). 8-Hydroxydeoxyguanosine (8-OHdG) and thioredoxin reductase (TrxR), representing oxidation and antioxidant levels, respectively, were analyzed as indices. Compared to the CA group, the RHSA group in the Pingshan and Jiangzha areas showed significantly decreased 8-OHdG levels ( Z = −3.350, −3.316, respectively, P < .05) and increased TrxR levels ( Z = 2.394, 3.773, respectively, P < .05). The RHSA and CA groups in Jiangzha had lower levels of TrxR and 8-OHdG compared to those in Pingshan. This finding may be related to the different radon concentration levels, bathing time and other factors. Results suggested that long-term bathing in radon hot spring may activate antioxidant function and reduce oxidative damage in the body.